Determinants of successful technology adoption among Malaysian cocoa farmers - Kasin, Ramle; Suandi, Turiman; Ismail, Maimunah; Krauss, Steven Eric (Universiti Putra Malaysia Press, 2012)
The contribution of group dynamics is considered crucial in group development. This paper looks at the role of group dynamic factors in predicting the successful adoption of technology by Malaysian cocoa farmer clusters. A systematic collection of data and information on cocoa farmer clusters in Malaysia with parameters investigated were group process, extension agents’ coordination ability and cocoa farmer clusters and extension agents’ demographic data. Discriminant analysis of the data on cocoa farmer clusters and extension agents were undertaken to verify the differences in the group dynamic factors between successful and less successful cocoa farmer clusters. The findings reveal that the roles of participation in cocoa farmer clusters, membership attraction to cocoa farmer clusters and cohesiveness in cocoa farmer clusters are likely to have higher possibility to cocoa farmer clusters’ success. In contrast, leadership and communication in cocoa farmer clusters were more likely to have low possibility to be successful.